Proposição metodológica interativa da “tecnologia social” como alternativa pró-sustentabilidade: pesquisa-ação com a COOCAT-MEL em Telêmaco Borba-PR - Silva, Heloísa de Puppi e (2015)
In addition to the questioning on the relevance of using the term “social technology” in STS studies, there is the pursuit of quantification and scaling of mutual impacts of technology and society. Something that is sustainable to a given social network cannot be considered the same by another one. Those are questions that come to light when one understands that every technology is social and that balance is made up out of imbalances. The objective is to propose an interactive methodology that captures the “social technology” in joint construction of pro- sustainability alternatives having a social local network. The research methodology chosen is predominantly qualitative and comprises: deductive procedures; participatory research; reflection; the deconstruction of the term "social technology"; the inversion of said research to an inductive method; inductive procedures; the reorganization of the epistemological, theoretical, methodological, operational and practical alignment; the redefinition of methods and research techniques; the choice of action research; until culminating in the proposal of a model. This is the result of research, which has as its form of analysis the implementation and practice of the proposal. It is about a model based on the principles of: essentiality to life; freedom; complexity; multi, inter and transdisciplinarity; and cyclic behaviour. It picks up the technology to build sustainability construction models that are characteristic of and peculiar to social networks, under the behaviour guidelines of: culture of life; democracy; joint construction; techniques and knowledge sharing; and of quality, productivity and optimization. It becomes feasible by the following procedures: agent preparation; identification of the social network; study and history of the social network and the site; action research; application of questionnaire; data tabulation and Social Network Analysis (SNA); joint construction of referrals; and an alternative to sustainability. This model has its uniqueness grounded in "social technology" and differs from the others by reflection and awareness of the social network as a way to enhance the individual before the social relations that he establishes when composing a new social balance. The set of procedures also distinguishes the model, which first proposes the learning of the agent which will conduct the capture and technological explanation of the network. The joint construction of the questionnaire is another difference so that the moments of said social network can be captured, proposing alternatives according to their identity. It is about a procedure to merge techniques and knowledge amongst the actors of the network. The social network was the Cooperative of Beekeepers and Meliponicultors Caminhos do Tibagi (Cooperativa dos Apicultores e Meliponicultores Caminhos do Tibagi; COOCAT-MEL) in Telêmaco Borba - Paraná - Brazil. From it, it was possible to frame a practical case model that had the technological explanation of the network as a result, with the presentation of the perceptions of times, satisfaction and joint construction as a measure of pro-sustainability alternatives of the network. The limits and weaknesses of the model are provided by complexity and by theoretical, operational and practical multidisciplinarity that resulted in the proposal of a Sustainability Lab to be continued in further studies.